The Effect of the Interplay of Gender and Ethnicity on Teachers Judgements: Does the School Subject Matter?. Issue 4 (13th July 2022) - Bonefeld, Meike; Kleen, Hannah; Glock, Sabine
Abstract: Two experimental studies investigated the disadvantages faced by female ethnic minority students when they are judged by pre- and inservice teachers. The results suggest that (preservice) teachers' judgments were affected by the judgment dimension. Study 1 revealed that teachers apply gender stereotypes in their judgments on mathematical ability: Teachers perceived female students' mathematical ability as lower than male students' mathematical ability. Furthermore, in Study 1 (inservice teachers) and Study 2 (preservice teachers) students' ethnicity influenced judgments on language proficiency. Beyond that, in Study 2 even judgments on mathematical ability were influenced by the information on students' ethnicity. However, the interplay of the student characteristics is crucial for preservice teachers while it is not for inservice teachers.